Generalized Pitzer Correlation for Density Calculations of Ionic Liquids - Nuqui, Jesus Patrick E.; Damalerio, Regina G.; Meas, Sychheng; Yem, Socheata; Soriano, Allan N (ASEAN Journal of Chemical Engineering, 2021)
The density of ionic liquids is an important design parameter for its utilization as a chemical process solvent. In this study, a generalized Pitzer-type correlation for calculating the density of ionic liquids with the use of reduced temperature (TR), reduced pressure (PR), and acentric factor (ω) as parameters is proposed. Experimental density data were obtained from several references through the IUPAC Ionic Liquids Database. Expansion of the terms as well as integrating the ionic liquid molecular weight was attempted to determine the accuracy improvement of the model in predicting densities at 0.1 MPa. Then, the obtained model was modified by further truncation to include the pressure effects for densities at higher pressures. MATLAB software was used to determine the optimal virial coefficients for the proposed correlations. The percent average absolute deviation (%AAD) was applied to calculate the variation between the experimental and calculated density values. It was concluded that the eight (8) coefficient correlation equation with molecular weight for densities at 0.1 MPa had a %AAD of 4.7537%. Upon modifying the correlation to include pressure effects, the resulting modified equation had an overall %AAD of 4.7174%.